Safety and Immunogenicity of a rAd35-EnvA Prototype HIV-1 Vaccine in Combination with rAd5-EnvA in Healthy Adults (VRC 012). - Michelle C Crank; Eleanor M P Wilson; Laura Novik; Mary E Enama; Cynthia S Hendel; Wenjuan Gu; Martha C Nason; Robert T Bailer; Gary J Nabel; Adrian B McDermott; John R Mascola; Richard A Koup; et al. (PLoS ONE)
Background VRC 012 was a Phase I study of a prototype recombinant adenoviral-vector serotype-35 (rAd35) HIV vaccine, the precursor to two recently published clinical trials, HVTN 077 and 083. On the basis of prior evaluation of multiclade rAd5 HIV vaccines, Envelope A (EnvA) was selected as the standard antigen for a series of prototype HIV vaccines to compare various vaccine platforms. In addition, prior studies of rAd5-vectored vaccines suggested pre-existing human immunity may be a confounding factor in vaccine efficacy. rAd35 is less seroprevalent across human populations and was chosen for testing alone and in combination with a rAd5-EnvA vaccine in the present two-part phase I study. Methods First, five subjects each received a single injection of 109, 1010, or 1011 particle units (PU) of rAd35-EnvA in an open-label, dose-escalation study. Next, 20 Ad5/Ad35-seronegative subjects were randomized to blinded, heterologous prime-boost schedules combining rAd5-EnvA and rAd35-EnvA with a three month interval. rAd35-EnvA was given at 1010 or 1011 PU to ten subjects each; all rAd5-EnvA injections were 1010 PU. EnvA-specific immunogenicity was assessed four weeks post-injection. Solicited reactogenicity and clinical safety were followed after each injection. Results Vaccinations were well tolerated at all dosages. Antibody responses measured by ELISA were detected at 4 weeks in 30% and 50% of subjects after single doses of 1010 or 1011 PU rAd35, respectively, and in 89% after a single rAd5-EnvA 1010 PU injection. EnvA-specific IFN-γ ELISpot responses were detected at four weeks in 0%, 70%, and 50% of subjects after the respective rAd35-EnvA dosages compared to 89% of subjects after rAd5. T cell responses were higher after a single rAd5-EnvA 1010 PU injection than after a single rAd35-EnvA 1010 PU injection, and humoral responses were low after a single dose of either vector. Of those completing the vaccine schedule, 100% of rAd5-EnvA recipients and 90% of rAd35-EnvA recipients had both T cell and humoral responses after boosting with the heterologous vector. ELISpot response magnitude was similar in both regimens and comparable to a single dose of rAd5. A trend toward more robust CD8 T cell responses using rAd5-EnvA prime and rAd35-EnvA boost was observed. Humoral response magnitude was also similar after either heterologous regimen, but was several fold higher than after a single dose of rAd5. Adverse events (AEs) related to study vaccines were in general mild and limited to one episode of hematuria, Grade two. Activated partial thromboplastin time (aPTT) AEs were consistent with an in vitro effect on the laboratory assay for aPTT due to a transient induction of anti-phospholipid antibody, a phenomenon that has been reported in other adenoviral vector vaccine trials. Conclusions Limitations of the rAd vaccine vectors, including the complex interactions among pre-existing adenoviral immunity and vaccine-induced immune responses, have prompted investigators to include less seroprevalent vectors such as rAd35-EnvA in prime-boost regimens. The rAd35-EnvA vaccine described here was well tolerated and immunogenic. While it effectively primed and boosted antibody responses when given in a reciprocal prime-boost regimen with rAd5-EnvA using a three-month interval, it did not significantly improve the frequency or magnitude of T cell responses above a single dose of rAd5. The humoral and cellular immunogenicity data reported here may inform future vaccine and study design. Trial registration ClinicalTrials.gov NCT00479999.